2011
DOI: 10.1371/journal.pone.0019706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of the Fitness Consequences of an Introduced Parasite of Darwin's Finches

Abstract: BackgroundIntroduced parasites are a particular threat to small populations of hosts living on islands because extinction can occur before hosts have a chance to evolve effective defenses. An experimental approach in which parasite abundance is manipulated in the field can be the most informative means of assessing a parasite's impact on the host. The parasitic fly Philornis downsi, recently introduced to the Galápagos Islands, feeds on nestling Darwin's finches and other land birds. Several correlational stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 40 publications
2
80
1
Order By: Relevance
“…Nests were dissected within 8 h of collection and P. downsi larvae, pupae, and eclosed pupal cases were counted. First instar larvae were not included in tallies of parasite abundance because they are too small to see reliably in the nest material (Koop et al, 2011). Total parasite abundance was calculated as the sum of all second and third instar larvae, pupae, and eclosed pupal cases found in a nest.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nests were dissected within 8 h of collection and P. downsi larvae, pupae, and eclosed pupal cases were counted. First instar larvae were not included in tallies of parasite abundance because they are too small to see reliably in the nest material (Koop et al, 2011). Total parasite abundance was calculated as the sum of all second and third instar larvae, pupae, and eclosed pupal cases found in a nest.…”
Section: Methodsmentioning
confidence: 99%
“…Adult females incubate the eggs and brood the offspring. Adult males do not sit on the nest and, therefore, do not appear to come into contact with the parasites (Huber et al, 2010; Koop et al, 2011). P. downsi was first documented in the Galapagos Islands in 1964 (Causton et al, 2006); however, it was not until 1997 that the fly was observed in large numbers in nests (Fessl et al, 2001; Fessl and Tebbich, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notorious example of an introduced parasite is the nest fly Philornis downsi, which has been implicated in the decline of critically endangered species of Darwin's finches, such as the mangrove finch (Camarhynchus heliobates) (O'Connor et al 2009, Fessl et al 2010. Several studies have shown that P. downsi reduces the reproductive success of the medium ground finch (Geospiza fortis) and other species of Darwin's finches (reviewed in Koop et al 2011). Once the eggs hatch, fly larvae feed on the blood of nestlings and adult females as they brood the nestlings.…”
mentioning
confidence: 99%
“…Adult flies, which are not parasitic, lay their eggs in the nests of finches and other land birds in the Galápagos. In some years, 100% of finch nests fail to produce fledglings due to P. downsi (Koop et al 2011, 2013a, O'Connor et al 2013. Several studies have shown that P. downsi reduces the reproductive success of the medium ground finch (Geospiza fortis) and other species of Darwin's finches (reviewed in Koop et al 2011).…”
mentioning
confidence: 99%